Logics - Nolt, John (Wadsworth Pub. Co., 1997)
This comprehensive introduction to symbolic logic covers informal logic and the syntax, semantics and metatheory of not only the classical propositional and predicate logics, but also for a number of extensions of classical logic and non-standard logics. It is the first textbook of this kind to provide substantive treatment of more recent developments in logic